Optimizing linear alkyl benzene sulfonate removal using fenton oxidation process in taguchi method - Khorsandi, H.; Mohammadi, A.; Kariminejad, F.; Haghighi, M.; Karimzadeh, S.; Khorsandi, J.; Aghapour, A.A. (Химия и технология воды, 2016)
Linear alkyl benzene sulfonate (LAS), which is the most common used anionic surfactant in detergents manufacturing, can discharge onto water resources through wastewater and causes change in taste and odor, disruption in water treatment processes, aquatics death, and oxygen transfer limitation. Accordingly, this article investigates to optimize LAS removal using Fenton oxidation process in Taguchi Method for the first time. LAS removal using Fenton oxidation was perused experimentally in a lab-scale reactor.